ANALYSIS OF TABOO WORDS IN JOKES A CASE STUDY AT (SAPA BARAT, MINAHASA SELATAN DISTRICT) - Suwu, Cici Chikita; Olii, Sanerita T.; Rorimpandey, Rinny (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
The purpose of the study is to discover the types of joking taboo words used by people in Sapa Barat jaga 2, Minahasa Selatan, where the people use several types of languages daily to communicate with family relatives, consisting of friends who understand each other. For the sample, the Researcher takes people aged 9 to 50, consisting of 5 children: three boys and two girls, and 15 adults, 10 men and five women. This study is qualitative research, and the Researcher used the theory by Miles and Huberman (1994). It consists of three steps: Data Reduction, Data Display, and Conclusion Drawing. The result of this study showed is that the taboo words in jokes at Sapa Barat, Jaga 2. Was Pendo, Cuki, Babi, Pemai, Kasta, Setang, Wusit, Keode, Cuka, Para, and Anjing. Based on the development, the Researcher concluded that people in Sapa Barat Jaga 2 frequently used taboo words in their marks with one another, with older or younger people, or with strangers to amuse themselves or feel satisfied.